2005
DOI: 10.1111/j.1468-0394.2005.00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Flexible flow shop scheduling: optimum, heuristics and artificial intelligence solutions

Abstract: For the past three decades or so the flexible flow shop (FFS) scheduling problem has attracted many researchers. Numerous research articles have been published on this topic. This study reviews research on the FFS scheduling problem from the past and the present. The solution approaches reviewed range from the optimum to heuristics and to artificial intelligence search techniques. I not only discuss the details from the selected methods and compare them, but also provide insights and suggestions for future res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(38 citation statements)
references
References 51 publications
0
35
0
3
Order By: Relevance
“…These include exact methods, heuristics, and metaheuristics. The present review fills in some of the gaps identified in previous reviews, like those of, [204,117,213] or more recently [151], and describes the most recent approaches. It also identifies research opportunities and proposes some interesting research lines.…”
Section: Introductionmentioning
confidence: 99%
“…These include exact methods, heuristics, and metaheuristics. The present review fills in some of the gaps identified in previous reviews, like those of, [204,117,213] or more recently [151], and describes the most recent approaches. It also identifies research opportunities and proposes some interesting research lines.…”
Section: Introductionmentioning
confidence: 99%
“…However, these uncertainties are not conventionally solvable. Moreover, since this mathematical programming problem resembles a flexible scheduling by existence of some stochastic variables, this makes the problem N P-hard to be solved [44]. For example, the availability variables or the release times to shop floor are stochastic that without any pre-assumptions is not possible to be solved conventionally.…”
Section: Conwip Simulation Scenariomentioning
confidence: 99%
“…1, the shop floor in the OEM plant consists of three steps of operations; in each step, three parallel machines work together, so that each machine has its unbounded buffer size in its predecessor. Indeed, this arrangement resembles a flexible flow shop scheduling problem [44] in generic context. This flexibility and the unbounded intermediate buffers avoid the blocking phenomena, while starvation is a frequent case in this problem.…”
Section: Conwip Simulation Scenariomentioning
confidence: 99%
“…A detailed survey for the FS problem has been given by Linn and Zhang [7] and Wang [8]. Moursli and Pochet [9] presented a branch-and-bound algorithm to minimize the makespan in FS.…”
Section: Literature Reviewmentioning
confidence: 99%